Pengaruh Komitmen Organisasi dan Kepuasan Kerja Terhadap Kinerja Dosen Swasta di Surabaya - Iswati Iswati; Jimmy Ignatius (Jurnal Simki Economic, 2023)
This study examines the Effect of Organizational Commitment on Job Satisfaction and Performance of Foundation Lecturers in Surabaya. In this study a descriptive research approach was used, while the type of sampling used was stratified random sampling involving 122 respondents, all of whom are foundation lecturers who teach in tertiary institutions with a minimum Masters and Doctoral degree and have worked as lecturers for at least 3 years. The location of the research was carried out in Surabaya and researched foundation lecturers. The analysis technique uses validity, reliability, classical assumption tests (including normality, multicollinearity and heteroscedasticity tests), while all hypotheses are tested using multiple linear regression to see the effect of each variable, with the SPSS application. The results of this study include Organizational Commitment has an effect on Job Satisfaction, Organizational Commitment has an effect on Lecturer Performance.